Female Labor Force Participation, Its Determinants and Effect on GDP in Pakistan - Ehsan, Saad (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2015)
This particular paper calculates the extra GDP that will be generated due to an increase in the female labor force participation in Pakistan. The extra GDP is computed by taking into account the “extra GDP per new employee” and “the number of new female employees entering the workforce”. The paper looks at the plausible GDP for the year 2011-2012 and 2013-2014 that might have taken place if the female labor force participation was equal to the hypothesized increased values instead of the actual participation rates. The paper sets up a hypothetical scenario. In the scenario the number of female and males in the labor force is assumed to be equal. This method sacrifices some realism in order to get a hypothesized GDP value. The reason for using this method is to show that raising labor force share of female has huge substantial GDP returns. We estimate that due to this labor force increase in Pakistan. The GDP of Pakistan goes up by almost 50%. The change is huge and substantial. The second part of the paper looks at the macro determinants of FLFP. For this purpose an econometric model is run based on previous studies. The results indicate that fertility is the main determinant for FLFP, while literacy is overvalued in determining FLFP. Keywords: gender equality, scenario analysis, female, labor force, Pakistan, North Cyprus.

ÖZ: Bu çalışma Pakistan’da kadın işgücü katılımına bağlı olarak doğan ekstra GSYİH’ yı hesaplamaktadır. Bu ekstra GSYİH ‘her yeni işçiye göre ekstra GSYİH’ ve ‘işgücüne katılan yeni kadın iş sayısı’ baz alınarak hesaplanmıştır. Bu araştırma 2011-2012 ve 2013-2014 yılları arasında kadın işgücü katılımı, asli katılım oranları yerine varsayılan artan değerlere eşit olursa yer alacak olan makul GSYİH’ yı araştırmıştır. Bu çalışma bir varsayımsal senaryo kurmuştur. Bu senaryoda kadın ve erkek işgücü sayısı eşit varsayılır. Bu yöntem varsayımsal GSYİH değeri elde etmek için bazı gerçeklikleri kaybeder. Bu yöntemi kullanma sebebi , kadın işgücü dağılımını artırmanın çok büyük ve önemli miktarda GSYİH geri dönüşü yaratacağını göstermesidir. Bunu Pakistan’ın işgücü artışına bağlı olarak elde ediyoruz. Bu değişim büyük ve önemlidir. Araştırmanın ikinci bölümünde FLFP’ nin makro belirteçleri incelenmektedir. Bu amaç için daha önceki çalışmalara dayalı olarak bir ekonometrik model oluşturulmuştur. Sonuçlar okuryazarlık FLFP için yüksek değerli olduğu sürece doğurganlığın FLFP için ana belirteç olduğunu gösteriyor. Anahtar Kelimeler: Cinsiyet Eşitliği, analiz , kadın , işgücü, Pakistan , Kuzey Kıbrıs
Master of Science in Economics. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Business and Economics, Dept. of Economics, 2015. Supervisor: Assoc. Prof. Dr. Fatma Güven Lisaniler.
Keywords: Economics; Women - Employment - Pakistan; Women - Labor and laborers; Women - Social conditions - Pakistan; gender equality; scenario analysis; female; labor force; Pakistan; North Cyprus